Poking in the fog - my personal access to digital humanities theory - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2019)
By accident, I started a Twitter-controversy about the necessity and existence of theory in Digital Humanities. On the way to my office early in the morning, I interpreted a quote of Franco Moretti as...